Morphological variation of Swertia chirayita (Roxb. ex Flem.) Karst - Raskoti, Bhakta B; Sakya, Shyam R (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.32-35